Aboveground versus soil‐mediated effects of an invasive grass on fire‐dependent forbs in an oak woodland - G. L. Williams; J. Stephen Brewer (Ecology and Evolution, 2024)
Abstract Most work on plant competition intensity in general has focused on how aboveground and belowground competition for resources between plants changes with soil resource availability. In contrast, much work on the competitive effects of non‐native invasive species on native species has focused on other mechanisms (e.g., allelopathy and microbial changes) and has largely ignored how these effects interact with mechanisms of resource competition along productivity gradients. We examined aboveground effects of an invasive grass, Microstegium vimineum, along with soil differences between invaded and non‐invaded areas on two native perennial herbs at a productive and an unproductive oak woodland site in north Mississippi, USA. We transplanted 32 individuals each of Helianthus silphioides and Potentilla simplex from uninvaded areas into natural patches dominated by M. vimineum at each of the sites. Each transplant was randomly assigned to a pot with either native soil or soil from around M. vimineum roots. Aboveground competition was manipulated by securing M. vimineum shoots in a non‐shading position around the transplant. We monitored survival of all transplants weekly in the growing seasons of 2020 and 2021. Transplant survival of H. silphioides was lowest in M. vimineum soil at the more productive site when M. vimineum was not pinned back. Transplant survival of P. simplex was lower at the more productive site but was mostly unresponsive to pinning and soil treatments. Synthesis. Our results suggest that soil‐mediated legacy effects of an invader may reduce some native species' ability to compete for light at productive sites.